Improving functional re-endothelialization of acellular liver scaffold using REDV cell-binding domain. (15th September 2018) - Devalliere, Julie; Chen, Yibin; Dooley, Kevin; Yarmush, Martin L.; Uygun, Basak E.
Graphical abstract: Abstract: Engineering of functional vascularized liver tissues holds great promise in addressing donor organ shortage for transplantation. Whole organ decellularization is a cell removal method that retains the native vascular structures of the organ such that it can be anastomosed with the recipient circulation after recellularization with healthy cells. However, a main hurdle to successful implantation of bioengineered organ is the inability to efficiently re-endothelialize the vasculature with a functional endothelium, resulting in blood clotting which is the primary cause of failure in early transplant studies. Here, we present an efficient approach for enhancing re-endothelialization of decellularized rat liver scaffolds by conjugating the REDV cell-binding domain to improve attachment of endothelial cells (EC) on vascular wall surfaces. In order to facilitate expression and purification of the peptide, REDV was fused with elastin-like peptide (ELP) that confers thermally triggered aggregation behavior to the fusion protein. After validating the adhesive properties of the REDV-ELP peptide, we covalently coupled REDV-ELP to the blood vasculature of decellularized rat livers and seeded EC using perfusion of the portal vein. We showed that REDV-ELP increased cell attachment, spreading and proliferation of EC within the construct resulting in uniform endothelial lining of the scaffold vasculature. We further observed that REDV-ELP conjugation dramatically reduced platelet adhesion and activation. Altogether, our results demonstrate that this method allowed functional re-endothelialization of liver scaffold and show great potential toward the generation of functional bioengineered liver for long-term transplantation. Statement of Significance: There is a critical need for novel organ replacement therapies as the grafts for transplantation fall short of demand. Recent advances in tissue engineering, through the use of decellularized scaffolds, have opened the possibility that engineered grafts could be used as substitutes for donor livers. However, successful implantation has been challenged by the inability to create a functional vasculature. Our research study reports a new strategy to increase efficiency of endothelialization by increasing the affinity of the vascular matrix for endothelial cells. We functionalized decellularized liver scaffold using elastin-like peptides grafted with REDV cell binding domain. We showed that REDV-ELP conjugation improve endothelial cell attachment and proliferation within the scaffold, demonstrating the feasibility of re-endothelializing a whole liver vasculature using our technique.